2016
DOI: 10.3390/polym8100353
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure of Sheared Entangled Solutions of Semiflexible Polymers

Abstract: Abstract:We study the influence of finite shear deformations on the microstructure and rheology of solutions of entangled semiflexible polymers theoretically and by numerical simulations and experiments with filamentous actin. Based on the tube model of semiflexible polymers, we predict that large finite shear deformations strongly affect the average tube width and curvature, thereby exciting considerable restoring stresses. In contrast, the associated shear alignment is moderate, with little impact on the ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(110 reference statements)
0
1
0
Order By: Relevance
“…Hence, the need of new models that better account the contribution of the concentration-dependent characteristic length scales (e.g., L e ) of the polymer network to its mechanical properties. In this regard, it is worth mentioning that microscopy studies on the tube width fluctuations in F-actin solutions have revealed the inappropriateness of theoretical approaches to employ a homogeneity (or mean-field) assumption, treating the tube radius as a constant, while experiments , and simulations indicate substantial heterogeneities. The common outcome of these studies indicates that both the concentration-dependent distributions of the tube radius P ( R e ) and of the entanglement length P ( L e ) are nonsymmetric Gaussian functions.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the need of new models that better account the contribution of the concentration-dependent characteristic length scales (e.g., L e ) of the polymer network to its mechanical properties. In this regard, it is worth mentioning that microscopy studies on the tube width fluctuations in F-actin solutions have revealed the inappropriateness of theoretical approaches to employ a homogeneity (or mean-field) assumption, treating the tube radius as a constant, while experiments , and simulations indicate substantial heterogeneities. The common outcome of these studies indicates that both the concentration-dependent distributions of the tube radius P ( R e ) and of the entanglement length P ( L e ) are nonsymmetric Gaussian functions.…”
Section: Discussionmentioning
confidence: 99%